(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
In the context of an increasing competition among Romanian universities for attracting students, developing a strong brand that appeals to the stakeholders‟ needs and desires, while incorporating the institutions values and principles, is a desired course of action. A well-structured relatable brand enables future students to identify themselves with an institution and helps them in taking an important decision that could determine the outcome of their future. The present study analyses the factors that high school students consider when choosing to attend a certain university, through a quantitative research performed among 275 high school students from 33 high school institutions in Bucharest, Romania. Result helped classify the most important markers of a reputable university, which universities should consider when building branding programs. At the same time, universities‟ communication strategies should appeal to values that they share with their targeted audiences in order to increase their attractiveness.